2007
DOI: 10.1002/adfm.200700506
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Performance of BaAl2O4 with a Wide Spectral Range of Optical Absorption

Abstract: Oxygen‐deficient BaAl2O4, with strong optical absorption in the spectra range from 200 to 2500 nm, was prepared by a simple and economic thermal treatment of BaAl2O4 in a H2 gas flow. Further studies found that a molar ratio of oxygen vacancies of about 0.4 % existed in the prepared oxygen‐deficient BaAl2O4 sample. The influence of oxygen vacancies on the electronic band structures and optical absorption of BaAl2O4 are elucidated via first principle calculations. Oxygen vacancies introduce impurity states abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…It is generally accepted that the oxygen vacancies often play a crucial role in surface applications such as heterogeneous catalysis. Recent studies indicate that higher photocatalysis activity can be achieved by the oxygen vacancies owning to the formation of narrow band gap [47,48]. Thus, the Cu 2 O-CuCl samples cloud present higher catalytic active than that of the Cu 2 O sample, although their have similar specific surface areas (Table 1).…”
Section: Epr Analysismentioning
confidence: 97%
“…It is generally accepted that the oxygen vacancies often play a crucial role in surface applications such as heterogeneous catalysis. Recent studies indicate that higher photocatalysis activity can be achieved by the oxygen vacancies owning to the formation of narrow band gap [47,48]. Thus, the Cu 2 O-CuCl samples cloud present higher catalytic active than that of the Cu 2 O sample, although their have similar specific surface areas (Table 1).…”
Section: Epr Analysismentioning
confidence: 97%
“…With respect to BaAl 2 O 4 formed during the fabrication process, it is unknown that whether it has a positive or negative influence on lubricating property of the Ni 3 Al matrix composites, since the lubricious performance of aluminate has not been explored. BaAl 2 O 4 , which belongs to the family of aluminate, has been studied for luminescent material and refractory cement applications [14][15][16]. The hexagonal structure of BaAl 2 O 4 consists of cornerconnected AlO 4 tetrahedra forming a tridymite related, tetrahedral framework sub-structure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that phosphor emission for this material is related to oxygen vacancies [16,18]. Specifically, BaAl 2 O 4 doped with Eu 2 þ causes no detectable decrease in O 2 À vacancies by H 2 (g), samples do not exhibit luminescence and the graph generated by Raman has an intensity line close to zero [19]. Unfortunately structural distortions due to oxygen vacancies are very difficult to visualize, even with the TEM technique.…”
Section: Pigmentsmentioning
confidence: 89%